The grip of sexual violence in conflict: feminist interventions in international law - Engle, Karen (Stanford studies in human rights, 2020)
Introduction -- Sexual Violence in Conflict and Women's Human Rights : A Genealogy -- Calling in the Troops -- Calling in the Judges : The Former Yugoslavia -- Calling in the Judges : Rwanda -- Calling in the Security Council for Women, Peace, and Security -- Epilogue : Beyond Social Death.